In a phrase, the non-alphabetical wordbooks - Gabrovšek, Dušan (Mostovi (Ljubljana), 2006)
The paper discusses general-purpose, mostly monolingual, non-alphabetical or partly alphabetical (mostly topical) English-language reference sources that leg behind the A-Z dictionary in overall importance.
Keywords: angleščina; leksikografija; slovarji; tezavri